A value-based analysis of the tourism use of agricultural heritage systems: Duotian Agrosystem, Jiangsu Province, China. Issue 12 (23rd July 2020) - Su, Ming Ming; Dong, Yuanzhou; Wall, Geoffrey; Sun, Yehong
Abstract: With worldwide industrialization and urbanization, agricultural heritage systems are under threat at the global scale despite their exceptional values reflecting intricate human-nature relationships. As a new function of agricultural heritage, tourism does not realize its potential for heritage conservation and community development. Therefore, the integration of multiple heritage values with tourism is highly important for sustaining agricultural heritage systems and rural communities. This study conceptualizes a multiple value system of agricultural heritage to analyze its tourism use and identify linkages for integration. With Duotian Agrosystem, a Globally Important Agricultural Heritage System (GIAHS) in China, as an example, this study identifies the mismatch between tourism demand and supply. Relying on the authenticity of Duotian agricultural landscape in Spring, current tourism is highly seasonal. Limited tourist experiences and ways for community participation are available without sufficient tourism expressions of the historical, socio-cultural, educational, and research values. As a result, the enhancement in livelihood value is restricted. Therefore, innovations are needed to construct diverse links between tourism and the multiple values of Duotian Agrosystem to enhance tourism contributions to heritage conservation and community development. Theoretical and management implications are then discussed in a broader context.